Auditory neuropathy in hyperbilirubinemia: Is there a correlation between serum bilirubin, neuron-specific enolase levels and auditory neuropathy? - TÜRKDOĞAN, DİLŞAD; SAVE, DİLŞAD; ÖZEK, EREN (TAYLOR & FRANCIS LTD, 2004)
This study evaluated whether a correlation exists between increased serum bilirubin and neuron-specific enolase (NSE) assays (a biochemical index of neuronal damage) and auditory neuropathy. Nineteen term neonates without hemolysis whose serum bilirubin levels were above 20 mg/dl and 27 healthy term newborns with bilirubin levels <13 mg/dl were included in the study. Auditory brainstem responses (ABRs) and transient evoked otoacoustic emissions (TEOAEs) of patients with hyperbilirubinemia were obtained before discharge. This preliminary study did not show any correlation between the serum NSE and bilirubin values. However, infants who had auditory neuropathy had significantly higher NSE levels, and thus these patients, being in the high-risk group, need close follow-up.
Keywords: hyperbilirubinemia; neuron-specific enolase; auditory brainstem response; transient evoked otoacoustic emissions; BRAIN-STEM RESPONSES; CEREBROSPINAL-FLUID; S-100 PROTEIN; HEARING-LOSS; COCHLEAR; INFANTS; POTENTIALS; MARKERS